Electrochemical determination of ethylvanillin based on LaV@GAC nanocomposite - Du, Haijun; Duan, Yu; Ai, Jixing; Kong, Dabin; Wang, Dexiang; Hu, Huali; Wang, Hong; Yang, Yang (Analytical sciences, 2023)
Ethyl vanillin (EVA) is widely used as a flavor additive in foods, and sensitive monitoring of EVA is of great significance for food safety. In this paper, the biomass of gum arabic derived carbon (GAC) coated with lanthanum vanadate (LaV) was constructed for the EVA sensor based on the synergistic effects of the electrochemical catalytic ability of LaV, the enhanced electrical conductivity with the GAC coating and the oxygen-containing functional groups in LaV@GAC. The as-developed LaV@GAC sensor showed a remarkable linear range from 0.06 μM to 100 μM and a low detection limit (LOD) of 6.28 nM. The electrochemical oxidation of EVA is limited by a diffusion-controlled process involving 2 electrons and 2 protons. Moreover, the LaV@GAC sensor has good recoveries (94.5–103.05%) for the detection of EVA in real milk powder samples. The proposed LaV@GAC sensor has good repeatability, high stability, and great potential for sensitive detection of flavor additives in food. Graphical abstract